Components of Panax ginseng and Rhodiola rosea regulate mitophagy via the SIRT1/3-PGC-1α-NRF2 pathway to improve myocardial ischemia-reperfusion injury - Yao, Ming; Wang, Xiaoli; Wei, Hongyu; Wang, Lisha; Zhang, Dongze; Liang, Zheng; He, Rong; He, Yuan; Jiang, Lihong; Cui, Yingzi (Frontiers in Pharmacology, 2026)
IntroductionThe combination of ginsenoside Rg1 and salidroside (PRC) exhibits cardioprotective potential against myocardial ischemia-reperfusion injury (MIRI), yet its underlying mechanism remains unclear.Materials and MethodsAn in vivo rat model of MIRI and an in vitro H/R model using H9c2 cardiomyocyte were established. PRC was administered, and its effects on myocardial injury, oxidative stress, mitochondrial function, and endothelial markers were evaluated. Key proteins in the SIRT1/3-PGC-1α-NRF2 pathway and mitophagy (Beclin 1, p62, PINK1, Parkin, TOM20) were analyzed by Western blot. The functional necessity of SIRT1/3 was validated using siRNA knockdown.ResultsPRC reduced infarct size, ameliorated mitochondrial ultrastructure, and attenuated oxidative stress in vivo. In vitro, PRC enhanced cell viability, restored ATP and mitochondrial membrane potential, and suppressed ROS production ROS. Mechanistically, PRC activated the SIRT1/3–PGC-1α–NRF2 axis, normalized PINK1/Parkin expression, preserved mitochondrial content (indicated by restored TOM20 levels), and inhibited excessive autophagy (evidenced by downregulated Beclin1 and upregulated p62). Notably, silencing SIRT1 or SIRT3 abolished these protective effects, confirming their essential upstream regulatory roles.ConclusionPRC attenuates MIRI by activating the SIRT1/3–PGC-1α–NRF2 pathway to modulate PINK1/Parkin-dependent mitophagy, thereby restoring mitochondrial homeostasis. Our study elucidates a novel mechanism underlying this natural product combination and highlights the SIRT1/3 axis as a promising therapeutic target for cardioprotection.